SKEPTIMISME AGAMA ISLAM DALAM CORETAN DINDING KOTA METRO - Irwansyah, Dedi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
Mural has been a common phenomenon in some big cities in Indonesia. While many people have utilized it constructively, few persons have used it to address certain messages which are not in line with the Islamic values. A serious study taking the mural as its research object is very rare. Thus, this writing is aimed at providing rich description on Islamic skepticism expressed through murals in the city of Metro. The data were approached through semiotics discipline and were analyzed qualitatively. The findings of the research show that Islamic skepticism were delivered through the use of certain symbols, borrowed methapor, imperative statement, Javanese diction, English word, code-switching, and intertextualityKeywords: Mural, Islam, religion skepticism, semiotics